Giraldi Cinthio on Romances - Giraldi, Giambattista Cinzio, 1504-1573 (Book collections on Project MUSE., 1968)
Giraldi Cinthio's Discorso intorno al comporre dei romanzi, here translated into English for the first time, was one of the most important critical works of the Renaissance. Written as a defense of Ariosto's Orlando Furioso, Giraldi's discourse is an inquiry both into the nature of poetry and into the characteristics of the ""heroic"" or epic genre, in which some of the world's richest poems fall. Henry L. Snuggs introduces this translation with an incisive interpretation of Giraldi's critical theory. Giraldi was the first, Snuggs states, to make a significant plea in sixteenth-century critici